PENERAPAN MODEL PEMBELAJARAN INSIDE OUT CIRCLE (IOC) UNTUK MENINGKATKAN HASIL BELAJAR IPA - Waruwu, Daswati (JURNAL PENA EDUKASI, 2018)
Abstract: This study aims to describe how the application of the Inside Out Circle (IOC) learning model learning model can improve the quality of learning in the subject matter of the excretion system class IX-A in SMP Negeri 3 Gunungsitoli academic year 2015/2016 and to describe how the learning model of the Inside learning model is applied Out Circle (IOC) to improve students' cognitive learning outcomes in the subject matter of the excretion system class IX-A in SMP Negeri 3 Gunungsitoli academic year 2015/2016. From the learning process that researchers do in the first (first) cycle the average learning outcomes reach 70.50. In the second cycle (two) the average learning outcomes reach 82.14. Suggestions that can be given by researchers based on the findings of the study is that this research is expected to provide input for Biology subject teachers in SMP Negeri 3 Gunungsitoli by applying the Inside Out learning model The Circle (IOC) is right on learning activities at school. So that it can motivate and assist students in Biology learning activities, especially in the subject matter of the excretion system. Keywords: Learning Outcomes, Inside Out Circle (IOC) Abstrak: Penelitian ini bertujuan untuk mendeskripsikan bagaimana penerapan model pembelajaran model pembelajaran Inside Out Circle (IOC) dapat meningkatkan kualitas pembelajaran pada materi pokok system ekskresi di kelas IX-A SMP Negeri 3 Gunungsitoli Tahun Pembelajaran 2015/2016 dan untuk medeskripsikan bagaimana penerapan model pembelajaran model pembelajaran Inside Out Circle (IOC) untuk meningkatkan hasil belajar kognitif siswa pada materi pokok system ekskresi di kelas IX-A SMP Negeri 3 Gunungsitoli Tahun Pembelajaran 2015/2016. Dari proses pembelajaran yang peneliti lakukan pada siklus I (pertama) rata-rata hasil belajar mencapai 70,50. Pada siklus II (dua) rata-rata hasil belajar mencapai 82,14.Saran yang dapat diberikan oleh peneliti berdasarkan temuan penelitian adalah penelitian ini diharapkan dapat memberikan masukan bagi guru mata pelajaran Biologi di SMP Negeri 3 Gunungsitoli dengan menerapkan model pembelajaran model pembelajaran Inside Out Circle (IOC) yang tepat pada kegiatan pembelajaran di sekolah. Sehingga dapat memotivasi dan membantu siswa dalam kegiatan pembelajaran Biologi khususnya pada materi pokok sistem ekskresi. Kata kunci: Hasil Belajar, Inside Out Circle (IOC)